The Design of Micro-class for Embedded Vocabulary Teaching in Senior High School - Yang, Zhufei; Zhao , Yang (Journal of Theory and Practice of Contemporary Education, 2023)
The author of this paper explored to embed a 5-8-minute small lesson in a 45-minute big lesson, and used this small lesson to make up for the differences in vocabulary learning ability of students who did not meet the teaching requirements of senior high school. This article is mainly about the design of embedded vocabulary makeup teaching micro-class, involving the definition of the subject, the principle of design, the principle of design, the function introduction of subdivision class type, and the design of teaching process and cases.